2005
DOI: 10.1128/aem.71.11.7389-7400.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Microbial Communities in Lake Pavin, a Unique Meromictic Lake in France

Abstract: The Bacteria and Archaea from the meromictic Lake Pavin were analyzed in samples collected along a vertical profile in the anoxic monimolimnion and were compared to those in samples from the oxic mixolimnion. Nine targeted 16S rRNA oligonucleotide probes were used to assess the distribution of Bacteria and Archaea and to investigate the in situ occurrence of sulfate-reducing bacteria and methane-producing Archaea involved in the terminal steps of the anaerobic degradation of organic material. The diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 41 publications
9
96
1
2
Order By: Relevance
“…Besides, the anoxic water compartment of Lake Kivu was also more diverse in types as pointed out by the richness estimations (p<0.02). It was previously suggested that anoxic environments maintain a higher diversity of energetic pathways and that this complexity permits the retention of higher metabolic and thus ecological diversity [3,84].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the anoxic water compartment of Lake Kivu was also more diverse in types as pointed out by the richness estimations (p<0.02). It was previously suggested that anoxic environments maintain a higher diversity of energetic pathways and that this complexity permits the retention of higher metabolic and thus ecological diversity [3,84].…”
Section: Discussionmentioning
confidence: 99%
“…It has a surface area of 2370 km 2 , a total volume of 580 km 3 , and a maximum depth of 485 m. Surface waters are considered to be oligotrophic with moderate primary production compared to other African lakes [22,23]. Further details on the hydrology, physicochemistry, and biology of the lake are published elsewhere [22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed a decrease of DGGE bacterial OTUs number with depth. Øvreås et al (1997) and Lehours et al (2005Lehours et al ( , 2007 also found that the structures of both the bacterial and archaeal communities in the anoxic zone of a meromictic lake changed with depth and the number of Bacterial OTUs bands decreased with depth. On the other hand, the numbers of Archaeal populations usually increased with depth (Øvreås et al 1997(Øvreås et al , Lehours et al 2005.…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…The 16S microarray approach is also subject to such bias, since the DNA analyzed on the array was generated by PCR. Both the 27F-927R (used for the clone libraries) and 27F-1492R primers (used for the 16S microarray) target all known bacteria and have been widely used in previous microbial ecological studies (5,14,18,20,27,30). Discrepancy in the assessment of bacterial diversity due to differences in the primer sets used was thus probably insignificant, especially given that all of the sequences identified in the clone libraries were detected by the array.…”
mentioning
confidence: 99%